Determination of the protection period of fungicides used for control of Sclerotinia stem rot in soybean through bioassay and chromatography - Miorini, Thomas J. J.; Raetano, Carlos Gilberto [UNESP]; Negrisoli, Matheus M. [UNESP]; Pérez-Hernández, Oscar (Springer Nature, 2021)
In Brazil, Sclerotinia stem rot (SSR) control in soybean depends primarily on application of the fungicides carbendazim, fluazinam, and procymidone. While these fungicides can provide effective control of the disease, their protection period, which is crucial for timing their optimal application, is poorly understood. In the present study, the protection period of carbendazim, fluazinam and procymidone was determined using a detached leaf bioassay (DLB) and chromatography. For the DLB, soybean plants were treated twice with each fungicide with or without mineral oil as adjuvant; leaves were collected at two or three-day intervals from 11 to 23 days, inoculated with Sclerotinia sclerotiorum mycelium, and the necrotic area was assessed 48 h after inoculation. For the chromatography test, each fungicide was applied and the leaves were collected every two days after treatment for 14 days. Fungicide residue concentration in tissue was determined according to a modified version of the quick, easy, cheap, effective, rugged and safe (QuEChERS) method. At 5, 7, and 9 days after the first application, fluazinam, carbendazim and procymidone, respectively, had no protective effect even when applied with mineral oil. Greater control efficacy was achieved after a second application. Fluazinam showed protective activity up to 4 days while carbendazim and procymidone showed about 10 days. The mineral oil only enhanced protection activity of procymidone in the second application. The analytical chemical separation indicated that the relative concentration of fluazinam decreased at a faster rate than that of carbendazim and procymidone. At day 14, the concentration of carbendazim and procymidone decreased from 34.97 to 9.39 mg kg−1, and 58.98 to 11.22 mg kg−1, respectively, suggesting that 10–14 days represent the approximate timing in spacing two consecutive applications. The knowledge of the protection period of these fungicides sets the basis to improving their timing of applications.
Keywords: Carbendazim; Fluazinam; Glycine max; Mineral oil; Procymidone; Sclerotinia sclerotiorum